A legislative reform to protect the rights of domestic workers in sri lanka: a critical analysis with relevant ilo conventions - Pathirana, M.P.S.K. (University of Jaffna, 2012)
Although Sri Lanka has ratified all eight core labour conventions declared by the International Labour Organization (ILO), the government has not taken specific measures yet to provide a national law concerning Domestic Workers, in order to protect and enhance the rights of domestic workers. According to the current situation of Sri Lanka, this sector has been recognized as being informal and not well-organized. In considering the Sri Lankan context, there are some differences between domestic workers and non-domestic workers in obtaining benefits and conditions from their workplaces. Domestic workers of Sri Lanka are expressly and impliedly excluded from its labour legislations. However, the ILO Convention on Decent Work for Domestic Workers 2011 demonstrates that the domestic workers should obtain all the benefits and conditions as the other sectors of employment attain. Therefore this research paper purported to make recommendations for a new separate legislation for the benefit of domestic workers including all the welfare measures, social security issues and effective problem solving mechanisms. Also it expects to propose certain amendments to the existing labour laws by including domestic workers into the scope of current legislations.
Keywords: Domestic workers; Social protection; Child domestic workers